All Days 2008
DOI: 10.2118/116130-ms
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Dispersion: A New Wireline Petrophysical Measurement

Abstract: Dielectric measurements and interpretation, introduced with great promise in the 1980s, have not found widespread use owing to measurement limitations, moderate accuracy, and insufficient quality control. This paper presents a new-generation dielectric tool that overcomes these limitations and brings extra information for more accurate petrophysical formation-evaluation. One of the revolutionary advances offered by this tool is the continuous measurement of dielectric dispersion (variation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(37 citation statements)
references
References 11 publications
0
35
0
1
Order By: Relevance
“…In addition, an indirect but cheap approach for formation permittivity acquirement is to use a socalled dielectric dispersion logging tool. This kind of wireline EM logging uses multispacing, multifrequency, and cross-polarization antenna arrays to measure attenuation and phase shift of EM wave in different radial depths (Hizem et al, 2008). Successful field tests have been reported that the tool can simultaneously inverse the permittivity and conductivity of the virgin formation (Mosse et al, 2009).…”
Section: Em Responsesmentioning
confidence: 99%
“…In addition, an indirect but cheap approach for formation permittivity acquirement is to use a socalled dielectric dispersion logging tool. This kind of wireline EM logging uses multispacing, multifrequency, and cross-polarization antenna arrays to measure attenuation and phase shift of EM wave in different radial depths (Hizem et al, 2008). Successful field tests have been reported that the tool can simultaneously inverse the permittivity and conductivity of the virgin formation (Mosse et al, 2009).…”
Section: Em Responsesmentioning
confidence: 99%
“…However, dielectric logging at frequencies of 1 GHz and above remains challenging in field measurements due to decreased depth of electric field penetration. On the contrary, currently available commercial dielectric tools operate at multiple spot frequencies [5] to facilitate a determination of water content and CEC: dielectric response at frequencies below 50 MHz is more affected by the surface effects described above [6]. At lower frequencies, clay content, geometry and spatial orientations of mineral rock constituents, and the salinity of pore fluid also affect the measured dielectric permittivity [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The dielectric scanner was developed to quantify complex permittivity at different frequencies (Hizem et al, 2008). Transmitters and receivers are mounted on a pad in contact with the borehole and raw measurement of attenuation and phase shift are obtained at four frequency points between 20 MHz to 1 GHz.…”
Section: Introductionmentioning
confidence: 99%